Oxidative stress status accompanying diabetic bladder cystopathy results in the activation of protein degradation pathways - Kanika, Nirmala (2010)
OBJECTIVES: To investigate the role that oxidative stress plays in the development of diabetic cystopathy. MATERIALS AND METHODS: Comparative gene expression in the bladder of non-diabetic and streptozotocin (STZ)-induced 2-month-old diabetic rats was carried out using microarray analysis. Evidence of oxidative stress was investigated in the bladder by analyzing glutathione S-transferase activity, lipid peroxidation, and carbonylation and nitrosylation of proteins. The activity of protein degradation pathways was assessed using western blot analysis. RESULTS: Analysis of global gene expression showed that detrusor smooth muscle tissue of STZ-induced diabetes undergoes significant enrichment in targets involved in the production or regulation of reactive oxygen species (P = 1.27 × 10(−10)). The microarray analysis was confirmed by showing that markers of oxidative stress were all significantly increased in the diabetic bladder. It was hypothesized that the sequelae to oxidative stress would be increased protein damage and apoptosis. This was confirmed by showing that two key proteins involved in protein degradation (Nedd4 and LC3B) were greatly up-regulated in diabetic bladders compared to controls by 12.2 ± 0.76 and 4.4 ± 1.0-fold, respectively, and the apoptosis inducing protein, BAX, was up-regulated by 6.76 ± 0.76-fold. CONCLUSIONS: Overall, the findings obtained in the present study add to the growing body of evidence showing that diabetic cystopathy is associated with oxidative damage of smooth muscle cells, and results in protein damage and activation of apoptotic pathways that may contribute to a deterioration in bladder function.